2016
DOI: 10.1103/physrevd.94.125016
|View full text |Cite
|
Sign up to set email alerts
|

Hadamard states for a scalar field in anti–de Sitter spacetime with arbitrary boundary conditions

Abstract: We consider a real, massive scalar field on PAdS d+1 , the Poincaré domain of the (d + 1)-dimensional anti-de Sitter (AdS) spacetime. We first determine all admissible boundary conditions that can be applied on the conformal boundary, noting that there exist instances where "bound states" solutions are present. Then, we address the problem of constructing the two-point function for the ground state satisfying those boundary conditions, finding ultimately an explicit closed form. In addition, we investigate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…The techniques used in [8] are rather flexible; they have been studied from a rigorous viewpoint in [9] and applied also to the analysis of a Klein-Gordon field in BTZ spacetime in [10]. In this paper, first we also apply them to the study of a massive, real scalar field in the global chart of CAdS n , in order to investigate if the results obtained in the Poincaré patch do extend globally.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The techniques used in [8] are rather flexible; they have been studied from a rigorous viewpoint in [9] and applied also to the analysis of a Klein-Gordon field in BTZ spacetime in [10]. In this paper, first we also apply them to the study of a massive, real scalar field in the global chart of CAdS n , in order to investigate if the results obtained in the Poincaré patch do extend globally.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper by two of us [8], it has been shown that, if one considers only the Poincaré patch of AdS n , it is possible to use a mode decomposition together with techniques proper of Sturm-Liouville problems, in order to prove that one can consider a whole one-parameter family of boundary conditions of Robin type, which include as a special case both the Dirichlet and the Neumann ones. In this work it has been shown that, for each of these boundary conditions, the Klein-Gordon equation can be solved in terms of initial data and unique fundamental solutions do exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We shall illustrate this fact by using the free Klein-Gordon theory as an example. Thus, our results also provide a bridge between the ideas of [30] and the concrete constructions in [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 82%
“…Recent works addressing this problem are [19,20,33], the latter extending the analysis of [31]. For specific choices of boundary conditions, there exist successful constructions of algebraic quantum field theories on spacetimes with timelike boundary, see e.g., [8,[10][11][12]. The main message of these works is that the algebraic approach is versatile enough to account also for these models, although some key structures, such as for example the notion of Hadamard states [11,32], should be modified accordingly.…”
Section: Introductionmentioning
confidence: 99%